Blended learning in permanent education of nursing professionals on smoking cessation - Fernanda Guarilha Boni; Lyana Duarte Borba Da Silva; Jamila Ivanise Grigolo; Solange Klockner Boaz; Ana Luísa Petersen Cogo; Isabel Cristina Echer (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To develop and validate the content of an educational intervention on smoking cessation for Nursing professionals using a Blended Learning approach. Method: A development and validation study by consensus of experts of the "Smoking Cessation" course for Nursing professionals on approaches to the smoking patient carried out in 2018. For refinement and validation of the final content, a convenience sample was made up of 12 professionals with expertise in the subject natter and an 80% consensus among the participants was considered. Results: The construction of the course involved the choice of subjects, production, and content validation. As a teaching strategy, Blended Learning was used, which has an interactive online stage and a face-to-face meeting to discuss concepts and exchange experiences. Conclusion: The course using a Blended Learning method proved to be innovative, low-cost, and with great capacity for disseminating knowledge, being an important ally to permanent education in health.